2020
DOI: 10.1128/msphere.00950-19
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Ingredients and Bakers on the Bacteria and Fungi in Sourdough Starters and Bread

Abstract: Sourdough starters are naturally occurring microbial communities in which the environment, ingredients, and bakers are potential sources of microorganisms. The relative importance of these pools remains unknown. Here, bakers from two continents used a standardized recipe and ingredients to make starters that were then baked into breads. We characterized the fungi and bacteria associated with the starters, bakers’ hands, and ingredients using 16S and internal transcribed spacer (ITS) rRNA gene amplicon sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 40 publications
2
59
0
Order By: Relevance
“…The bacterial and fungal species present in sourdough originate from (a) the microflora of the flour, (b) the bakeries' environment microbiota, (c) the water used and, according to some researchers, (d) the bakers themselves (their bodily microbiome) [178]. Typically, in the biomass of sourdough, it is mostly the Lactobacillus strains producing acid and yeasts who undertake the production of carbon dioxide.…”
Section: Sourdoughmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial and fungal species present in sourdough originate from (a) the microflora of the flour, (b) the bakeries' environment microbiota, (c) the water used and, according to some researchers, (d) the bakers themselves (their bodily microbiome) [178]. Typically, in the biomass of sourdough, it is mostly the Lactobacillus strains producing acid and yeasts who undertake the production of carbon dioxide.…”
Section: Sourdoughmentioning
confidence: 99%
“…Some studies, however, have highlighted a different population dynamic and point to a greater variety of bacteria and yeasts other than Lactobacillus and Saccharomyces [179][180][181][182]. Other studies have revealed that, at the genus level, Enterococcus, Lactococcus, Lactobacillus, Leuconostoc, Pediococcus, Streptococcus and Weissella are associated with sourdough production [177,178]. In the above micro-ecological niche, the genus Lactobacillus is dominant.…”
Section: Sourdoughmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, S. cerevisiae is the most widespread species found in sourdoughs [40] made by bakers, but also in sourdough made by farmersbakers [41,42]. It can be found as the dominant species in sourdough, even in bakeries where no industrial starter is used, suggesting that the species may colonize a sourdough from the bakery's environment or the baker's hands [43]. Therefore, bakery strains of S. cerevisiae may have undergone different domestication processes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of citizen science microbiology projects focus on bacteria, there are several related to mycology. Kew's Lost and Found Fungi project asks volunteers to hunt for 100 mushrooms in the UK that are rare or potentially extinct (fungi.myspecies.info/content/ lost-and-found-fungi-project), the Mushroomfinder app developed by the University of Vienna records mushroom observations across Austria (www.univie.ac.at/oemykges/ pilzfinder-at/), and the Global Sourdough Project identified bacteria and yeasts in sourdough starters sent in by bakers from around the world (Reese 2020). Both Slovenia (www.invazivke.si) and the UK (www.livingashproject.org.…”
mentioning
confidence: 99%